Real-time morphological detection of label-free submicron-sized plastics using flow-channeled differential interference contrast microscopy - Han, Jiyun; Park, Subeen; Seid, Mingizem Gashaw; Park, Byeongho; Lee, Soo Hyun; Kim, Hyung Min; Lee, Changha; Lee, Jaesang; Kim, Jae Hun; Hong, Seok Won (Elsevier BV, 2023)
Owing to the surge in plastic waste generated during the COVID-19 pandemic, concerns regarding microplastic pollution in aqueous environments are increasing. Since microplastics (MPs) are broken down into submicron (< 1 & mu;m) and nanoscale plastics, their real-time morphological detection in water is necessary. However, the decrease in the scattering cross-section of MPs in aqueous media precludes morphological detection by bright-field microscopy. To address this problem, we propose and demonstrate a differential interference contrast (DIC) system that incorporates a magnification-enhancing system to detect MPs in aqueous samples. To detect MPs in both the stationary and mobile phases, a microfluidic chip was designed, taking into consideration the imaging depth of focus and flow resistance. MPs of various sizes flowing in deionized, tap, and pond water at varying speeds were observed under Static and Flow conditions. Successful real-time morphological detection and quantification of polystyrene beads down to 200 nm at a constant flow rate in water were achieved. Thus, the proposed novel method can significantly reduce analysis time and improve the size-detection limit. The proposed DIC microscopy system can be coupled with Raman or infrared spectroscopy in future studies for chemical composition analysis. Environmental implication: Microplastics (MPs), particularly submicron plastics < 1-& mu;m, can pose a risk to human health and aquatic ecosystems. Existing methods for detecting MPs in the aqueous phase have several limitations, including the use of expensive instruments and prolonged and labor-intensive procedures. Our results clearly demonstrated that a new low-cost flow-channeled differential interference contrast microscopy enables the realtime morphological detection and quantification of MPs down to 200 nm under flowing conditions without sample labeling. Consequently, our proposed rapid method for accurate quantitative measurements can serve as a valuable reference for detecting submicron plastics in water samples.